Business Cycle Synchronization in the EMU: Core vs. Periphery - Ansgar Belke; Clemens Domnick; Daniel Gros (Global Labor Organization (GLO), 2017)
This paper examines business cycle synchronization in the European Monetary Union with a special focus on the core-periphery pattern in the aftermath of the crisis. Using a quarterly index for business cycle synchronization by Cerqueira (2013), our panel data estimates suggest that it is countries belonging to the core that are faced with increased synchronization among themselves after 2007Q4, whereas peripheral countries decreased synchronization with regards to the core, non-EMU countries and among themselves. Correlation coefficients and nonparametric local polynomial regressions corroborate these findings. The usual focus on co-movements and correlations might be misleading, however, since we also find large differences in the amplitude of national cycles. A strong common cycle can thus lead to large differences in cyclical positions even if national cycles are strongly correlated.
Keywords: E32; F15; R23; 330; Business cycles; core-periphery; EMU; local polynomial regressions; synchronicity